On the importance of balance to aesthetic plating - Velasco, C; Michel, C; Woods, A; Spence, C (Elsevier, 2016)
Traditionally, the visual composition of food on a plate, or plating, has often taken place in an intuitive manner. In restaurants, plating is refined through an iterative process until the composition ‘just feels right’, often driven by the experienced whim of the chefs working at the ‘pass’. Increasingly, though, science is starting to deliver insights that could explain, or disconfirm, the chefs’ intuitions and ‘rules-of-thumb’. Recently, researchers interested in the aesthetics of food have started to assess people’s overall preferences when it comes to the visual composition of food on the plate, and the impact that this may have on the consumption experience. The research shows that principles borrowed from the visual arts can, to a certain extent, be applied to plating. In experimental aesthetics, one assertion that is often made is that people prefer balanced over unbalanced visual compositions. Here, we report on a series of citizen science experiments conducted at the Science Museum, in London, that demonstrate a clear preference for balanced over unbalanced presentations of exactly the same ingredients over all compositions. This preference for balanced plating is considered in light of the recent trend by many modernist chefs toward asymmetric plating (i.e., when all of the edible elements are crowded onto just one side of the dish).